Secure mobile VoIP - Talevski, Alex; Chang, Elizabeth; Dillon, Tharam S. (IEEE, 2007)
The rapid growth of computing, the Internet and telecommunications systems have resulted in a broad range of ways to communicate and access information. Voice over Internet Protocol (VoIP) is a Computer Telephony Integration (CTI) solution that transports voice traffic over a data network as an alternative to the Plain Old Telephone Service (POTS). VoIP products promise converged telecommunications and data services that are cheaper, more versatile and provide higher voice quality as compared to traditional offerings. Although VoIP products are rapidly gaining market share with home users, uptake in the enterprise market has remained slow as a result of security and mobility concerns. This paper addresses the issues surrounding VoIP security and mobility through the integration of robust security features into a lightweight VoIP protocol that is tailored for mobile devices. A theoretical approach is realized with the development of a software prototype whose security and mobility properties are analyzed.